2022
DOI: 10.1161/jaha.121.023207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronary Microvascular Disease and Coronary Vasospasm in Patients With Nonobstructive Coronary Artery Disease: Systematic Review and Meta‐Analysis

Abstract: Background A relevant proportion of patients with suspected coronary artery disease undergo invasive coronary angiography showing normal or nonobstructive coronary arteries. However, the prevalence of coronary microvascular disease (CMD) and coronary spasm in patients with nonobstructive coronary artery disease remains to be determined. The objective of this study was to determine the prevalence of coronary CMD and coronary vasospastic angina in patients with no obstructive coronary artery disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 80 publications
3
70
0
4
Order By: Relevance
“…Fractional flow reserve (FFR) was calculated as the ratio between distal coronary pressure and central aortic pressure (P d and P a , respectively) during saline-induced hyperaemia. CFR was defined as the ratio between absolute hyperaemic flow (Q hyp ) and absolute resting flow (Q rest ) 16. MRR was calculated with the previously validated formula:17…”
Section: Methodsmentioning
confidence: 99%
“…Fractional flow reserve (FFR) was calculated as the ratio between distal coronary pressure and central aortic pressure (P d and P a , respectively) during saline-induced hyperaemia. CFR was defined as the ratio between absolute hyperaemic flow (Q hyp ) and absolute resting flow (Q rest ) 16. MRR was calculated with the previously validated formula:17…”
Section: Methodsmentioning
confidence: 99%
“…Coronary Flow Reserve (CFR) was defined as the ratio between absolute hyperemic flow (Q hyp ) and absolute resting flow (Q rest ), using a cut-off of 2.5 for pathological values (21). Microvascular Resistance Reserve (MRR) was calculated with the previous validated formula (17):…”
Section: Microcirculation Assessment With Intracoronary Continuous Th...mentioning
confidence: 99%
“…Patients with NOCAD had a high prevalence of CMD irrespective of sex. Sara et al established that 64% of the NOCAD patients were evaluated to have CMD [ 15 ], while a recent meta-analysis by Mileva et al revealed a 41% prevalence of CMD among NOCAD patients [ 16 ]. The clinical manifestation of CMD may be associated with inappropriate, extensive vasoconstriction and/or the impaired relaxation of arterioles and prearterioles; this reduces the supply of blood to cardiomyocytes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%